2021
DOI: 10.1155/2021/6673292
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Severity, Rate, and Causes of Moral Distress among Nursing Students: A Cross-Sectional Study

Abstract: Background. One of the most important psychosocial issues related to the nursing profession is moral distress (MD), which has devastating effects on student performance as well as patient care. The current study was conducted to determine the frequency, severity, rate, and causes of MD in nursing students. Methods. During this cross-sectional study, 86 samples were last year undergraduate nursing students of Kermanshah University of Medical Sciences, who were entered into the study by the census method. Data g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Regarding moral distress, the respondents are experiencing low moral distress; this means that they may not be affected by the harmful effects of high levels of moral distress like indifference and pessimism about nurses and decrease interest in their profession [18]. This finding is also parallel to the results of [19] during the pre-COVID-19 pandemic and [7] during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 58%
“…Regarding moral distress, the respondents are experiencing low moral distress; this means that they may not be affected by the harmful effects of high levels of moral distress like indifference and pessimism about nurses and decrease interest in their profession [18]. This finding is also parallel to the results of [19] during the pre-COVID-19 pandemic and [7] during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 58%
“…It is important to describe how various factors contribute to moral distress in nursing students during their clinical experience and professional training. Moral distress may affect their educational qualification [1,22,23].…”
Section: Situations That Cause Moral Distress In Studentsmentioning
confidence: 99%
“…One problem that nurses experience as a result of ethical dilemmas is moral distress. Moral distress is a problem experienced by nurses when they know the appropriate action to take, but are forced to take action that is completely opposite to their personal and professional values [1][2][3]. Studies have shown that moral distress is a common serious problem.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations